The Criminal Liability of The Defamation Perpetrators Against The President or Vice President After Having The Court Decision Number Constitutional 013-022 / Puu-Iv / 2006 - Dyas Tazza Ulima (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2018)
Base on the interest to Realize the goals of the state, Indonesia Gives the power to the president as the representative of the state to run the government rate and its existence is highly protected. One of the Efforts to protect the president and vice president is by setting the criminal sanctions Relating to crimes againts the dignity of the precident or vice president of the which stipulated in Article 134, 136 bis and 137 of the Criminal Code. However, there must be a deeper study with the application of Reviews These provisions. It is Because there are some shifts have happended towards the provisions after having the Constitutional Court Decision Number 013-022 / PUU-IV / 2006. Formulation of the problem in this research is about the rule and the criminal liability of the perpetrators defamation against the president or vice preseident after having the Constitutional Court Decision Number 013-022 / PUU-IV / 2006. The method used is the which is legal research with statute approach, conceptual approach and comparative approach, through a comparison of the Criminal Code in the Netherlands, Germany and Thailand. The result in this reasearch shows that after the Constitutional Court Decision Number 013-022 / PUU-IV / 2006, the rule defamation against the president or vice president of the personal qualities addresed to be subject to the rules of Chapter XVI Criminal Code. In the case of defamation addresed to the president or vice president as an official of the State, be subject to the rules of Article 207 Criminal Code. In addition to the Criminal Code, the rules can be applied Also regulated under the Broadcasting Act and the Information and Electronic Transactions Act. Moreover, the subject of the which can be burdened with the criminal liability is an individual (base on the rules in the Criminal Code and the Broadcasting Act); individual and corporation (base on the rules in Information and Electronic Transactions Act);